A Novel Technique for the Fabrication of Maxillary Obturator Using Combination of PEEK, Acrylic Resin, and Silicone for Partial Maxillectomy Patient - Patil, Abhijit A.; Patil, Sarika Abhijit; Sabane, Ajay V.; Kalsekar, Bhagyashree; Patil, Seema S. (Medical Research and Its Applications Vol. 11, 2024)
This case report is an attempt to describe clinical and laboratory steps for the fabrication of a Maxillary obturator using a combination of PEEK, Polymethyl Methacrylate (PMMA), and Silicone for a patient with Aramany Class II defect. Polyethertetherketone (PEEK) has been advocated for medical use for many years because of its unique mechanical and biological properties. Recently many researchers proposed and successfully demonstrated the use of PEEK as a material of choice for various prosthodontic treatment modalities. We report a case of a 37-year-old male patient with the primary complaint of hypernasality and discomfort due to a partial maxillectomy performed for squamous cell carcinoma. Clinical examination revealed an Aramany Class II defect. The patient was presented with partial maxillectomy with Aramany Class II defect and seeking treatment to improve his speech, mastication, and function. PEEK was chosen as a material of choice for the fabrication of the framework based on properties like biocompatibility, inertness, low density, and ease of processing. PEEK can be successfully used combined with acrylic resin for the fabrication of a definitive obturator and is a good substitute for conventional materials like cobalt-chromium and titanium alloys. The direct retainer components of the PEEK framework showed acceptable retentive properties. Also, the weight of the prosthesis was significantly reduced. Overall, the patient was satisfied with the function, esthetic, and comfort of the prosthesis.